Posyandu Cadres On Capacity Building: Prevent Stunting By Improving Nutrition During The First 1000 Days Of Life - Nita Dwi Astikasari; Sumardiyon (Universitas STRADA Indonesia, 2023)
The Indonesian Ministry of Health initiated the “The First 1000 Days of Life Program” to decline the prevalence of stunting and other malnutrition problems. However, it turns out that the society and Posyandu cadres still do not understand about stunting, the first 1000 days of life, and early detection of stunting. This community service program was carried out in July-August 2018 using the community relations method. The program participants were posyandu cadres in Ngara-arap Village, Ngaringan District, Grobogan Regency, totaling 25 people (22 people participated in the program until the end). The program includes advocacy and self-development activities, education to posyandu cadres regarding stunting, education to posyandu cadres regarding the first 1000 days of life in stunting prevention, training on measuring body length and height for toddlers, and evaluation monitoring. The results of the program include: 1) 88% of the target is participating in the program to the end, 2) There is an increase in cadres' knowledge about stunting and nutrition during the first 1000 days of life after participating in the program as measured by the pre-post test questionnaire (there is an increase in the average pre-test and post-test scores). test of 0.7 points), 3) As many as 60% of the cadres were able to practice how to measure body length and height of toddlers measured by observation, and 4) 40% of posyandu cadres were willing to transfer knowledge to society through posyandu.